Indirect taxation of monopolists: A tax on price - Henrik Vetter (Kiel Institute for the World Economy (IfW), 2012)
A digressive tax like a variable rate sales tax or a tax on price gives firms an incentive for expanding output. Thus, unlike unit and ad valorem taxes which amplify the harm from monopoly, a digressive tax lessens the harm. We analyse a tax on price with respect to efficiency and practical policy appeal. Using a tax on price in combination with ad valorem taxation it is possible to achieve the Ramsey solution. That is, the combination of the two taxes secures tax revenue in the least distortive way. We also show how tax reforms based only on observation of price and quantity can make use of a tax on price in order to improve welfare. That is, it is practical to use a tax on price.
Keywords: H21; L31; 330; tax on price; ad valorem tax; tax incidence